The choice of proton pump inhibitor in terms of efficacy and safety in a particular patient - Umrzaqov Odil bek (Genius Journals, 2023)
Proton pump inhibitors are a diverse class of drugs with unique acid suppression properties . The aim of this work was to present the therapeutic benefits of rabeprazole and pantoprazole in clinical practice. Numerous studies have demonstrated the high efficacy of proton pump inhibitors and the relative safety of taking these drugs. However, it is necessary to increase the awareness of doctors and pharmacists about the possibility of complications during therapy with proton pump inhibitors in a polymorbid patient. The choice of proton pump inhibitors should be based on the clinical situation, comorbidity and therapy, the presence of risk factors in the patient, the speed and stability of the drug effect.
Keywords: proton pump inhibitors; rabeprozole; pantaprazole